Preparing Science Librarians for Success: An Evaluation of Position Advertisements and Recommendations for Library Science Curricula. - A. R. DeArmond; E. A. Overhauser; S. M. Powell; L. R. Schelling; A.D. Oster; M.K. Palos; K.K. Sago (Issues in Science and Technology Librarianship)
Science librarianship is a rapidly changing professional specialization that requires unique skills and experiences for science librarians to perform at the highest level. A content analysis of recent job advertisements was conducted to determine the most desirable qualifications for science librarians. It was found that the most frequently cited qualifications include formal education and professional experience, and also, significantly, interpersonal skill sets in areas such as customer service, communication, and teaching. Furthermore, subject-specific scientific knowledge and experience was also found to be desirable for science librarian positions or departmental liaison roles. These results suggest that library schools should re-evaluate their curricula to make sure that their courses emphasize communication skills and offer subject-specific training as well as education in the traditional skills of librarianship. [ABSTRACT FROM AUTHOR]